2002
DOI: 10.1016/s0960-9822(02)00753-4
|View full text |Cite
|
Sign up to set email alerts
|

Exocytosis: The Many Masters of the Exocyst

Abstract: The exocyst is a conserved eight-subunit complex involved in the docking of exocytic vesicles. The exocyst has now been identified as an effector for five small GTPases, including Sec4, Rho1, Rho3, Cdc42 and, most recently, RalA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
156
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(160 citation statements)
references
References 19 publications
3
156
0
1
Order By: Relevance
“…Recent insights into structure of the exocyst have shed light on the architecture and function of this complex, suggesting that the exocyst assembles into an overall rodlike structure, in the process bridging the vesicles to their target membrane (5,6). Consistent with this notion, the exocyst has been found to concentrate on "hotspots" on the plasma membrane where exocytosis actively takes place and has been implicated in different types of membrane trafficking including polarized growth in yeast, neurite growth in the nervous system, glucose transport in fat cells, and basal-lateral trafficking in epithelial cells (4). Interestingly, in Saccharomyces cerevisiae and Schizosaccharomyces pombe, the exocyst complex localizes to the cleavage furrow and is essential for membrane delivery during cytokinesis (7)(8)(9).…”
mentioning
confidence: 68%
“…Recent insights into structure of the exocyst have shed light on the architecture and function of this complex, suggesting that the exocyst assembles into an overall rodlike structure, in the process bridging the vesicles to their target membrane (5,6). Consistent with this notion, the exocyst has been found to concentrate on "hotspots" on the plasma membrane where exocytosis actively takes place and has been implicated in different types of membrane trafficking including polarized growth in yeast, neurite growth in the nervous system, glucose transport in fat cells, and basal-lateral trafficking in epithelial cells (4). Interestingly, in Saccharomyces cerevisiae and Schizosaccharomyces pombe, the exocyst complex localizes to the cleavage furrow and is essential for membrane delivery during cytokinesis (7)(8)(9).…”
mentioning
confidence: 68%
“…Because vesicle tethering takes place before SNARE-mediated membrane fusion, spatial and temporal regulation of the exocyst is crucial to determining where and when exocytosis takes place. Consistent with this notion, the exocyst has been found to be under the control of a number of small GTPases in a variety of cells (for review, see Novick and Guo 2002;Lipschutz and Mostov 2002). In this article, we focus on the roles of the Rab and Rho proteins.…”
Section: Spatial and Kinetic Control Of Membrane Trafficking By Smallmentioning
confidence: 81%
“…Whereas the yeast exocyst communicates with several members of the Rho subfamily of small GTPases, including Cdc42p (Lipschutz and Mostov, 2002;Novick and Guo, 2002), in mammals, only RAL (RALA) and TC10 (RHOQ) GTPases have been shown to bind the exocyst (Inoue et al, 2003), and no link has been reported with CDC42. Recently, genetic and biochemical evidence have shown that both yeast and mammalian exocysts communicate with the ER-translocon via an interaction with the Sec61␤ subunit (Lipschutz et al, 2003;Toikkanen et al, 2003), suggesting a role in protein synthesis/translocation events.…”
Section: Introductionmentioning
confidence: 99%